GPR137-RAB8A activation promotes ovarian cancer development via the Hedgehog pathway - Chao Tang; Lin Li; Chongying Zhu; Qiang Xu; Zihao An; Shouying Xu; Chao Lin (Journal of Experimental & Clinical Cancer Research)
Abstract Background Ovarian cancer (OC) progression is one of the commonest cause of female cancer death. While treatments in clinic includes primary surgery and targeted chemotherapy, curative and survival trends in OC have not significantly improved. Thus, further investigation of the mechanisms regarding OC carcinogenesis and discovery of novel targets is of great importance. Methods Human ovarian tissue specimens, RNA sequencing, GEPIA database and bioinformatics analyses were used to analyze the gene correlation, and to identify and validate potential downstream candidates. The biological effects of GPR137-RAB8A-Hedgehog(HH) were investigated using in vitro and in vivo models and methods including qRT-PCR, RNA stability assay, RNA immunoprecipitation assay, GLI-luciferase reporter assay, nucleo-cytoplasmic separation assay, membrane-cytoplasmic separation assay, western blot, co-immunoprecipitation, immunofluorescence staining, cell counting kit-8 assay, wound healing assay, matrigel invasion assay, colony formation assay, xenografts assay, in situ transplantation tumor model of ovarian cancer in nude mice, and immunohistochemistry staining. Results GPR137 expression was significantly higher in collected clinical OC tissues, compared with the adjacent normal tissues. Consistently, suppression of GPR137 inhibited human SK-OV-3 and A2780 OC cell proliferation, migration, invasion, and colony formation, whereas overexpression of GPR137 in human OC HO8910 cell exerted the opposite effects on cell biological behaviors. Mechanistically, RAB8A was identified as a downstream target of GPR137, and GPR137 promotes RAB8A expression by promoting RAB8A mRNA stability. By RNA-sequencing and experiments in vitro using multiple ovarian cancer cell models as well as in vivo using subcutaneous xenografts assay and in situ transplantation ovarian cancer model in nude mice, we further demonstrated that RAB8A positively mediated OC progression through activating HH signaling pathway by disassociating the protein–protein complex formation of GLI and SuFu (Suppressor of Fused), which reciprocally enhanced GPR137 activity, forming a regulation loop between HH signaling and GPR137. Conclusions Collectively, this study depicts the role of GPR137-RAB8A-HH cascade in the development of OC, deepening our understanding of tumor biomechanics regarding OC progression and providing novel targets for OC therapy in future.